Population-level analysis of migratory phenology using genomic data in a migratory songbird - Bobowski, Taylor, author; Ruegg, Kristen, advisor; Anderson, Eric, committee member; Cohen, Emily, committee member; Horton, Kyle, committee member (Colorado State University. Libraries, 2022)
The timing of spring migration for Nearctic-Neotropical birds is key for maximizing access to seasonal resources, such as food or territory on the breeding grounds, while minimizing risk of exposure to winter conditions. Many factors, including sex, weather, energetic condition, and food availability influence migration timing. However, the methods for disentangling within and between population drivers of migratory timing have historically been limited by challenges associated with identifying the breeding location of migrants passing through stop-over sites. For example, spring phenology hypotheses predict that the timing of migration will be driven by the date of spring onset at the breeding grounds, but spring onset often co-varies with distance to breeding site, making it difficult to disentangle the relative roles of each. Here, we utilize genomic data to identify the breeding ground of origin for over one thousand Common Yellowthroats (Geothlypas trichas) collected at key migratory stopover points to test the relative roles of sex, migration distance, and date of spring onset in driving migratory timing. We found different relationships for analyses at the species and population level. We conclude that while sex, estimated migration distance, genetic population, and breeding ground phenology are all highly significant predictors of migratory timing across the species, the relative importance each factor differs among genetically distinct populations and from the species-level pattern. Our results highlight the importance of including population-level differences when attempting to understand the multitude of factors that regulate migratory timing.